Analisis Yuridis Mekanisme Pengundangan Peraturan Daerah Provinsi Kepulauan Riau - Farid, Miftah (Universitas Internasional Batam, 2018)
A statutory regulation starts to apply and has binding power on the date of promulgation. Enactment is intended to fulfill the formal requirements of a law and to fulfill the principle of legal fiction that everyone is considered to know the law. The enactment of the Provincial Regulation is the authority of the Provincial Regional Secretary whose mechanism of enactment is carried out by the Legal Bureau of the Regional Secretariat of the Riau Islands Province. However, the implementation of the promulgation mechanism carried out by the Legal Bureau of the Regional Secretariat of Riau Islands Province is different from the guidelines set out in the Minister of Home Affairs Regulation No. 80 of 2015 in addition to the disharmony between the laws and regulations relating to enactment.The method used in this research is normative juridical method with qualitative juridical data analysis method. The implementation of the enactment mechanism carried out by The Legal Bureau of the Regional Secretariat of the Riau Islands Province is still not in accordance with the Minister of Home Affairs Regulation No. 80 of 2015 in addition to the need for legal rules governing the mechanism of enactment in more detail and clearness.